Determination of Network Technology of Fixed Broadband with Fuzzy Multiple Criteria for Decision Making Method - Juanda Wijaya (Publindo Akademika, 2021)
To get the concept of developing an effective and efficient fixed broadband network, it is necessary to standardize fixed broadband access network technology. This standardization will facilitate in determining the design and development costs of the overall access network. In this paper, the process of determining the standardization of access networks is discussed through the Fuzzy SWOT MCDM (Multiple Criteria Decision Making) method. The process that is made is by establishing the SWOT access network technology that is available then the ranking process is carried out with fuzzy MCDM algorithm from the results of the questionnaire provided by network experts at PT. Indosat, one of the telecommunications network and service providers in Indonesia.